2011
DOI: 10.1089/pop.2010.0015
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Cost-Effective Care with a Patient-Centric Chronic Obstructive Pulmonary Disease Program

Abstract: Coronary obstructive pulmonary disease (COPD) is an escalating health problem for individuals, their families, and the public at large, resulting n considerable morbidity and mortality. A 1-year pilot program was conducted at a managed care medical group to empower COPD patients with self-management skills and improve their quality of life through enhancing cost-effective care. A total of 141 COPD patients were enrolled in the intervention group that imparted self-management principles, and provided telephonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 6 publications
0
28
0
1
Order By: Relevance
“…Another example of case management success was reported by Chuang, Levine, & Rich (2011) studying 141 patients with COPD. This study evaluated the effects of patient education, frequent case management contact with the patient and a specific action plan for symptom exacerbation (Chuang et al, 2011). The results of this study showed an overall decrease in paid claims, an increase in primary care physician contact, and a downward trend in hospital admissions, bed-days and ER visits for the intervention group (Chuang et al 2011).…”
Section: Cost-effectiveness Of Case Managementmentioning
confidence: 95%
See 2 more Smart Citations
“…Another example of case management success was reported by Chuang, Levine, & Rich (2011) studying 141 patients with COPD. This study evaluated the effects of patient education, frequent case management contact with the patient and a specific action plan for symptom exacerbation (Chuang et al, 2011). The results of this study showed an overall decrease in paid claims, an increase in primary care physician contact, and a downward trend in hospital admissions, bed-days and ER visits for the intervention group (Chuang et al 2011).…”
Section: Cost-effectiveness Of Case Managementmentioning
confidence: 95%
“…Two easily replicated and inexpensive methods -regular calls from a case manager and discharge information cards reduced repeat suicide attempts by 8% (Vaiva et al, 2011). Another example of case management success was reported by Chuang, Levine, & Rich (2011) studying 141 patients with COPD. This study evaluated the effects of patient education, frequent case management contact with the patient and a specific action plan for symptom exacerbation (Chuang et al, 2011).…”
Section: Cost-effectiveness Of Case Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] While tobacco consumption in the United States is in decline, the continued increase in incidence of COPD may be associated with increased smoking among women. [10][11][12] More women than men have died of this progressive disease since 2000, 11,12 and recent findings suggest that severe, early-onset COPD may be associated with female sex and other factors. 13 The availability of respiratory treatment guidelines 2,6,14 has not prevented increasing hospitalization rates for patients with COPD (1990COPD ( -2005.…”
Section: Introductionmentioning
confidence: 99%
“…6 Multicomponent disease management approaches, which incorporate patient self-management empowerment, effective transitions across care settings, and engaging and interfacing with pulmonary specialists when clinically indicated, may reduce the risk of repeated hospitalization, thereby improving patient quality of life and cost of care. 10,[23][24][25][26] This article focuses on the important role of the hospitalist in improving disease management, and highlights how care transitions can be improved to empower patients with COPD to better manage their disease.…”
Section: Introductionmentioning
confidence: 99%